ROLE OF EDUCATION IN SUPPORTING REGIONAL COMPETITIVENESS - Widayanti, Baiq Harly; Rahmawati, Diah; Harisandi, Dicky; Imansyah, Imansyah (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2024)
Amal Usaha Muhammadiyah (AUM) is an educational institution that contributes to producing a competent society. Since the establishment of Muhammadiyah as an Islamic organization has committed to producing quality generations through education. This research aims to find out the readiness of AUM education in supporting regional competitiveness and recommendations for improving AUM education can be more optimal in supporting regional competitiveness. The method uses qualitative with the variables studied are human resources, infrastructure, financing, and graduates. The analysis method uses descriptive and SWOT analysis. The results are AUM has been ready in supporting the competitiveness of the region as seen from the conformity of AUM vision with the regional vision, the number of teachers and educators is in accordance with the ratio of student numbers, facilities for skills improvement are available although still limited, have various sources of financing and cooperation in supporting learning activities. The recommendation are: AUM needs to increase the quantity and quality of learning support facilities and improve the atmosphere of academic learning especially related to the needs of the revolution 4.0 era. Improve the quality of the entrepreneurship curriculum; establish and strengthen career centers, strengthen cooperation with various parties, and improve professional teaching staff and educators.